Potential of primary drug prevention of cardiotoxicity in the context of anticancer therapy - Yu. A. Vasyuk; E. Y. Shupenina; E. O. Novosel; D. A. Vyzhigin; A. G. Nosova; L. G. Zhukova; D. A. Filonenko; E. I. Khatkova (Российский кардиологический журнал, 2023)
Aim. To search early signs of cardiotoxicity in patients receiving anticancer therapy and evaluate the effectiveness of cardioprotection with an angiotensin-converting enzyme inhibitor, beta-blocker and myocardial cytoprotector.Material and methods. The study included 98 patients with high and very high risk of cardiotoxicity according to the Mayo Clinic scale (USA). Cancer patients with hypertension were offered cardioprotective treatment with a fixed-dose combination of perindopril and bisoprolol, and patients with very high risk and concomitant coronary artery disease additionally trimetazidine.The patients were divided into 2 following groups: the experimental group (n=50), where patients were prescribed cardioprotective therapy, and the control group (n=48), which consisted of patients who refused or had contraindications to cardioprotection. All patients underwent an examination, including the collection of complaints and anamnesis, physical examination, electrocardiography and echocardiography with an assessment of left ventricular (LV) global longitudinal strain before chemotherapy and 1, 3, 6, 9 and 12 months after initiation of anticancer therapy.Results. In patients of the control group, by the end of the follow-up, the left atrial volume index and LV end-diastolic volume index significantly increased. In the main group, these indicators did not change significantly. In the control group, by the final visit, the LV ejection fraction significantly decreased in comparison with the initial value and the value in the first group. After 6, 9 and 12 months, there was a significant decrease in the LV global longitudinal strain in the control group, while in the main group this indicator remained within the normal range. The mortality rate in the control group was significantly higher (15% vs 2% in the experimental group). In the experimental group, cardiotoxic complications occurred in 28%, while in the control group — in 78% of patients.Conclusion. The study demonstrated the significant importance of cardiac monitoring and primary drug prevention of cardiotoxicity of anticancer therapy. A sig nificant deterioration in LV systolic function was shown in patients with a high and very high risk of cardiotoxicity who did not receive cardioprotective therapy, while its high efficiency was demonstrated in patients of the experimental group.